A Content Analysis of English Textbook “English For Nusantara” for 7 Grade Junior High School in Kurikulum Merdeka - Melania Indar Nur Febraningrum; Bambang Suroso (UM Purwokerto Press, 2023)
This study aims to analyze English textbook entitled English for Nusantara for grade 7 junior high school students at the Kurikulum Merdeka and to find out all the strengths and the weaknesses of this book in the items aims and approach, language content, skills, topic, methodology, and practical consideration determined by Cunningsworth's theory (1995). The method used in this study is a qualitative descriptive method with content analysis and literature study. The subjects in this study are the 5 chapters contained in the English for Nusantara textbook. In collecting data, the writer makes a table and evaluates each item determined from Cunningsworth's theory (1995). In data analysis techniques, the percentage of item fulfillment is calculated by dividing the total criteria met by the total number of criteria for each item then multiplied by 100%. Then determine the strengths and the weaknesses of each of these items. The results of this study indicate that the English textbook English for Nusantara fulfills an average of 94% in the